2012
DOI: 10.1186/1479-5876-10-134
|View full text |Cite
|
Sign up to set email alerts
|

Exosome removal as a therapeutic adjuvant in cancer

Abstract: Exosome secretion is a notable feature of malignancy owing to the roles of these nanoparticles in cancer growth, immune suppression, tumor angiogenesis and therapeutic resistance. Exosomes are 30–100 nm membrane vesicles released by many cells types during normal physiological processes. Tumors aberrantly secrete large quantities of exosomes that transport oncoproteins and immune suppressive molecules to support tumor growth and metastasis. The role of exosomes in intercellular signaling is exemplified by huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
302
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 357 publications
(308 citation statements)
references
References 129 publications
4
302
0
2
Order By: Relevance
“…Consistent with a number of previous studies (10,(25)(26)(27), 786-0 cell-derived exosomes were observed to increase the formation of tubular stuctures in HUVECs compared with the control group. However, the underlying molecular mechanism of this effect remains unclear.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Consistent with a number of previous studies (10,(25)(26)(27), 786-0 cell-derived exosomes were observed to increase the formation of tubular stuctures in HUVECs compared with the control group. However, the underlying molecular mechanism of this effect remains unclear.…”
Section: Discussionsupporting
confidence: 79%
“…The tumor cell-derived exosome is known to manipulate the surrounding microenvironment to promote angiogenesis, invasion and metastasis, as well as escape immune surveillance (10). In the present study, exosomes secreted from the human renal cancer cell line, 786-0, were found to facilitate tubular formation via regulation of hepaCAM and VEGF expression of HUVECs.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Glycosylation-targeted capture of exosomes is also the basis for an upcoming plasmapheresis device, Aethlon’s hemopurifier. The hemopurifier is a hollow fibre cartridge functionalised with lectins and antibodies, to be used with dialysis systems for the extracorporeal capture of circulating exosomes from blood [85]. Tumour-derived exosomes are directly immunosuppressive in some contexts [86] and can also sequester immunotherapeutic antibodies through antigen display [87].…”
Section: Clinical Perspectives On Ev Glycosylation and The Potentialmentioning
confidence: 99%
“…Recent study showed that exosomes removal might be an adjuvant therapy for malignancies due to the vital roles of these cell-derived microparticles in therapeutic resistance. 109 The intuitive mechanisms of drug resistance involving exosomes might be the sequestration of cytotoxic drugs in the intracellular microvesicles and the subsequent expulsion, to wipe out drug effect within the cells. 110 The results of Luciani et al 111 are in accord with the above conclusion and demonstrated that lymphoma, adenocarcinoma, and melanoma cells confiscated drugs such as vinblastin, 5-flurouracil, and cisplatin in their endosomal compartments.…”
Section: Exosomes As Communicators Of Drug Resistance In Lymphomamentioning
confidence: 99%